Clinical, diagnostic imaging and histopathological features of equine malignant melanoma causing femoral nerve paresis - M. L. Souhail; C. Daniel; L. Wilson; B. Mather; Z. Khan; J. Del‐Pozo; M. McMaster; P. Kelly (Equine Veterinary Education, 2026)
Summary The study describes a grey Connemara pony presented with progressive severe right hindlimb lameness (4/5 AAEP scale), caused by a space‐occupying melanoma leading to femoral nerve (FN) and spinal cord (SC) compression. The pony had a firm swelling over the right lumbar region and atrophy of the ipsilateral quadriceps muscle group. Although the neurological findings were suggestive of FN paresis, the underlying cause remained uncertain; therefore, nuclear scintigraphy was selected as the advanced imaging modality to further investigate the lesion in this case. The final diagnosis was made through the conventional cytology and histopathology. Given the extensive appearance of the melanoma in this case, no therapeutic intervention was deemed to rapidly improve the pony's pain levels, prompting euthanasia on welfare grounds. The post‐mortem examination identified malignant melanoma extending from L3 to L6, invading into adjacent skeletal muscle and compressing the SC. These findings were supported by the post‐mortem CT and MRI. Due to the position and dimension of the melanoma, it was most likely compressing the emergence of the FN. The use of scintigraphy has not been previously reported as an aid tool in diagnosing melanoma in horses.